2017
DOI: 10.3168/jds.2017-12750
|View full text |Cite
|
Sign up to set email alerts
|

Management practices for male calves on Canadian dairy farms

Abstract: Morbidity, mortality, and antimicrobial use and resistance are major concerns in the rearing of male dairy calves, so information to support disease prevention is important. The objective of this cross-sectional study was to describe management practices associated with the care of male calves during their first days of life on Canadian dairy farms. A survey was completed by dairy producers across Canada between March 1 and April 30, 2015. The survey included 192 questions covering producer background, farm ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 25 publications
4
74
1
1
Order By: Relevance
“…One of the major challenges with veal production is that veal producers rely on dairy producers to provide the necessary care of these calves on the dairy farm of origin before departure. As a minority (9%) of Canadian dairy producers did not always feed colostrum to male calves (Renaud et al, 2017), this is an area that needs to be addressed to improve the health and welfare of male calves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major challenges with veal production is that veal producers rely on dairy producers to provide the necessary care of these calves on the dairy farm of origin before departure. As a minority (9%) of Canadian dairy producers did not always feed colostrum to male calves (Renaud et al, 2017), this is an area that needs to be addressed to improve the health and welfare of male calves.…”
Section: Discussionmentioning
confidence: 99%
“…Improved energy status protects against disease and supports immune function (Todd et al, 2017). It has been reported that 17% of surveyed Canadian dairy source farms providing inferior nutrition to male calves compared with female calves (Renaud et al, 2017), and this, combined with the energy expenditure and mobilization occurring during calf transport (Knowles et al, 1999), means that many male calves enter the veal industry with suboptimal energy status and low body fat cover (Wilson et al, 2000). Serum concentrations of BHB, nonesterified fatty acids (NEFA), cholesterol, glucose, and urea could all serve as markers of energy status in calves.…”
Section: Introductionmentioning
confidence: 99%
“…were male, for which the care on source farms is sometimes questioned. However, at least a study on Canadian 307 farmers reported that 91% of the farmers administered colostrum to all male calves (Renaud et al, 2017). The concentrations of other APPs were not associated with elapsed time to antimicrobial treatments.…”
Section: Use Of Antimicrobials 290mentioning
confidence: 95%
“…Unfortunately, the welfare of bull calves is frequently overlooked given they often leave the farm within a week or two after birth and are often of low value (Holden & Butler, ). In Canada, 17% of dairy farmers stated that they did not provide the same quantity of food to male calves compared to heifer calves, and using blunt force was a common method among the 5% of farmers that reported having euthanized at least one male calf at birth in the last year (Renaud, Duffield, LeBlanc, Haley, & Kelton, ). Long distance transport of young male “bobby” calves in Australia to slaughter plants is of grave concern, with approximately 0.6% of calves dying during transport due to adverse environmental stressors (Cave, Callinan, & Woonton, ).…”
Section: Semen Selectionmentioning
confidence: 99%